Modelling economic hysteresis losses caused by sunk adjustment costs - Matthias Göcke; Jolita Matulaityte (Philipps-University Marburg, School of Business and Economics, 2015)
Transition from one economic equilibrium to another as a consequence of shocks is often associated with sunk adjustment costs. Firm specific sunk market entry investments (or sunk market exit costs) in case of a reaction to price shocks are an example. These adjustment costs lead to a dynamic supply pattern similar to hysteresis. In analogy to "hysteresis losses" in ferromagnetism, we explicitly model dynamic adjustment losses in the course of market entry and exit cycles. We start from the micro level of a single firm and use explicit aggregation tools from hysteresis theory in mathematics and physics to calculate dynamic losses. We show that strong market fluctuations generate disproportionately large hysteresis losses for producers. This could give a reason for the implementation of stabilizing measures and policies to prevent strong (price) variations or, alternatively, to reduce the sunk entry and exit costs. However, the explicit inclusion of uncertainty (associated with an option value of waiting) is shown to reduce economic hysteresis losses.
Keywords: B59; C61; D21; D69; 330; sunk-cost hysteresis; adjustment costs; dynamic losses; path-dependence; persistence; option value of waiting